(untitled) (Universal International Scientific Journal, 2026)
This article examines the changes in human needs from the time of their emergence to the present day and their impact on the environment from a philosophical and psychological perspective. The following is an analysis of the extinction of biological species and the impact of the human factor on this. The main part of the article is devoted to the connection between A. Maslow’s pyramid of needs and Z. Freud’s personality structure. It comparatively sheds light on the driving power of the concept of "Identity" (ID), the managerial role of the "Self" (Ego) and the importance of the laws and regulations of society (Super-Ego) in the formation of personality. It also scientifically substantiates the need for a person to consciously control his ego, using the example of problems such as moral vices in modern society - gambling and pornography.